The effect of pressure gradient and abrasive tool wear when polishing ceramic tiles - Amiril Sahab, Abdul Sani; Sousa, Fábio José Pinheiro (Elsevier Ltd, 2020)
A series of experimental investigations were conducted to develop and describe the distribution of the pressure gradient below and across the topological surface of laboratory grinding tools on a ceramic tile during the gloss gaining process. The possibility of controlling the pressure required for the industrial polishing ceramic tiles would prevent excessive wear, directly reducing energy and water consumption. The present research aims to determine the effect of incremental surface pressure distribution in the polishing of ceramic tiles with line contact. For this purpose, two grinding devices were mounted together as a polishing head and built from the machine's base coordinate system on a CNC tribometer with a deflection angle of 2.2°. The grinding pressure was distributed gradually underneath and across the polishing tools by implementing a new polishing tool composed of a rotating shaft with pivot joint, helical springs, and two abrasive blocks attached to it. Due to the configuration of polishing tools with preferred process parameters, the impact of the material removal and gloss production was found to be minimized or maximized according to the chosen kinematics. Results implied that the process outcome in terms of gloss level and fine surface finish is influenced by the surface pressure (maximum at approximately more than 15 MPa) as well as the abrasive tool surface wear. Furthermore, in the manufacturing line, a higher wear rate is posed by the coarser abrasives but less wear rate on the finer abrasives with high gloss gaining.